Coping with jet-lag: A Position Statement for the European College of Sport Science - Reilly, T.; Atkinson, G.; Edwards, B.; Waterhouse, J.; Åkerstedt, T.; Davenne, D.; Lemmer, B.; Wirz-Justice, A. (European Journal of Sport Science, 2007)
Elite athletes and their coaches are accustomed to international travel for purposes of training or sports competition. Recreational participants are similarly, if less frequently, exposed to travel stress. Transient negative effects that constitute travel fatigue are quickly overcome, whereas longer-lasting difficulties are associated with crossing multiple time-zones. Jet-lag is linked with desynchronization of circadian rhythms, and its impact depends on the duration and direction of flight, flight schedule, and individual differences. Athletes' performances are likely to be affected for some days until the body clock is readjusted in harmony with local time. Knowledge of the physiological characteristics of the body clock can be used to develop behavioural strategies that accelerate readjustment, in particular the timing of outdoor or bright light exposure, perhaps melatonin ingestion, meals, and exercise. Attempts to promote sleep by use of drugs that adjust the body clock, induce sleepiness or promote wakefulness are relevant but discouraged in travelling athletes. Support staff should develop appropriate education programmes for their athletes who can then make informed choices about their behaviour and minimize the transient effects of jet-lag on their well-being and performance.